Cold Atmospheric Plasma as a Novel Therapeutic Tool for the Treatment of Brain Cancer - Adhikari, Manish; Adhikari, Bhawana; Adhikari, Anupriya; Yan, Dayun; Soni, Vikas; Sherman, Jonathan; Keidar, Michael (Current Pharmaceutical Design, 2020)
Background: Studies from the past few years revealed the importance of Cold Atmospheric Plasma (CAP) on various kinds of diseases, including brain cancers or glioblastoma (GBM), and hence coined a new term ‘Plasma Medicine’ in the modern world for promising therapeutic approaches. Here, we focus on the efficacy of CAP and its liquid derivatives on direct interactions or with specific nanoparticles to show pivotal roles in brain cancer treatment. Method: In the present review study, the authors studied several articles over the past decades published on the types of CAP and its effects on different brain cancers and therapy. Results: A growing body of evidence indicates that CAP and its derivatives like Plasma Activated Media/ Water (PAM/PAW) are introduced in different kinds of GBM. Recent studies proposed that CAP plays a remarkable role in GBM treatment. To increase the efficacy of CAP, various nanoparticles of different origins got specific attention in recent times. In this review, different strategies to treat brain cancers, including nanoparticles, are discussed as enhancers of CAP induced targeted nanotherapeutic approach. Conclusion: CAP treatment and its synergistic effects with different nanoparticles hold great promise for clinical applications in early diagnosis and treatment of GBM treatment. However, results obtained from previous studies were still in the preliminary phase, and there must be a concern over the use of optimal methods for a dosage of CAP and nanoparticles for complete cure of GBM.
Keywords: glioblastoma